2021
DOI: 10.1002/ejic.202100501
|View full text |Cite
|
Sign up to set email alerts
|

Half‐Sandwich (η6‐Benzene)Ruthenium(II) Complex of Picolyl Functionalized N‐Heterocyclic Carbene as an Efficient Catalyst for Thioether Directed C−H Alkenylation of Arenes

Abstract: In this report, a half-sandwich (η 6 -benzene)Ru(II) complex of picolyl functionalized N-heterocyclic carbene was synthesized and efficiently used for the alkenylation arenes through thioether directed CÀ H bond activation. The thioether functionality of the substrate directed a selective ortho-vinylation through CÀ H bond activation. Moreover, reaction significantly works under mild reaction conditions than the previously reported ones which use the precious noble metal catalyst including the Pd(II), Rh(III),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The synthesis methodology for the Ru­(II) catalyst is shown in Scheme . An earlier known procedure was employed for the synthesis of 1-(2-chloroethyl)-1 H -benzimidazole (a), , and a slightly modified procedure directed us to 1-(2-(phenylselane)­ethyl)-1 H -benzimidazole (b). , Further, a reaction of 1-(2-(phenylselane)­ethyl)-1 H -benzimidazole and 2-bromomethyl pyridine resulted in N -(1-selanophenyl-2-ethyl)- N ″-(pyridine-2-ylmethyl) benzimidazolium bromide (c), which is our desired ligand for the complexation. Finally, a silver carbene transfer reaction of ligand c with Ag 2 O in CH 2 Cl 2 under a N 2 atmosphere at room temperature and in the dark, followed by the addition of a methanol suspension of [η 6 (C 6 H 6 )­RuCl­(μ-Cl)] 2 to the resulting solution of silver complex produces complex 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis methodology for the Ru­(II) catalyst is shown in Scheme . An earlier known procedure was employed for the synthesis of 1-(2-chloroethyl)-1 H -benzimidazole (a), , and a slightly modified procedure directed us to 1-(2-(phenylselane)­ethyl)-1 H -benzimidazole (b). , Further, a reaction of 1-(2-(phenylselane)­ethyl)-1 H -benzimidazole and 2-bromomethyl pyridine resulted in N -(1-selanophenyl-2-ethyl)- N ″-(pyridine-2-ylmethyl) benzimidazolium bromide (c), which is our desired ligand for the complexation. Finally, a silver carbene transfer reaction of ligand c with Ag 2 O in CH 2 Cl 2 under a N 2 atmosphere at room temperature and in the dark, followed by the addition of a methanol suspension of [η 6 (C 6 H 6 )­RuCl­(μ-Cl)] 2 to the resulting solution of silver complex produces complex 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis methodology for the Ru(II) catalyst is shown in Scheme 2. An earlier known procedure was employed for the synthesis of 1-(2-chloroethyl)-1H-benzimidazole (a), 30,31 and a slightly modified procedure directed us to 1-(2-(phenylselane)ethyl)-1H-benzimidazole (b). 30,31 Further, a reaction of 1-(2-(phenylselane)ethyl)-1H-benzimidazole and 2-bromomethyl pyridine resulted in N-(1-selanophenyl-2ethyl)-N″-(pyridine-2-ylmethyl) benzimidazolium bromide (c), which is our desired ligand for the complexation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Their strong σ-donor properties and ease of stereo-electronic modification at nitrogen substituent and carbon backbones of the heterocyclic skeleton have been utilized in the development of complexes with interesting properties and excellent catalytic activities. [6][7][8][9][10][11] A new subclass of NHCs, called protic-NHCs (pNHCs), which bears at least one NH functional group in the N-heterocyclic ring, has become popular in recent years with contributions from Hahn, Ikariya, Kuwata, and several other groups. [12][13][14][15][16][17][18][19][20] The pNHCs have attracted significant attention over the classical NHCs due to the existence of a proton-responsive NH group, allowing H-bonding interactions, β-deprotonations, and nucleophilic additions.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, chalcogen atoms have great potential to act as directing groups; moreover, these atoms also provide an inherent stability to the molecules. 6 Among the chalcogens, selenium has great potential to act as an efficient directing group without poisoning metal catalysts. 7 In 2020, Tang et al revealed the first instance of Se-directed C−H bond borylation of arene.…”
mentioning
confidence: 99%